Pinch hit - Green, Tim, 1963- (HarperCollins, 2012)
"When movie star Trevor and regular Little League player Sam discover that they are identical twins who were separated at birth, they decide to trade places for a while so that Sam can live the Hollywood life and Trevor can play baseball"--